Linear and non-linear association of chronic kidney disease with retina and choroid vessel density in diabetes: a prospective study - Lijian Fang; Ruiheng Zhang; Suoqing Zhuang; Lei Wang; Qiuping Wang; Yong Huang; Mingli Wang; Yu Feng; Min Xiao; Chunyuan Zhou; Lili Wu; Sihan Zhang; et al. (Photodiagnosis and Photodynamic Therapy)
Purpose: To investigate the association of retinal and choroidal vessel density with renal function using optical coherence tomographic angiography (OCTA). Method: The present study prospectively recruited consecutive diabetes patients admitted to Beijing Liangxiang Hospital from October 2023 to March 2024. All participants underwent comprehensive ophthalmologic examinations and laboratory analysis at the first visit. Quantitative parameters of OCTA scans included retinal superficial vascular complex (SVC) and deep vascular complex (DVC) vessel densities, and choriocapillaris flow deficits (CCFD%). Results: A total of 85 patients were included in the present study. After adjusting for severity of diabetic retinopathy and other confounding factors, every 1 % increased SVC within in ETDRS grid was associated with reduced incidence of CKD (OR=0.86 95 %CI:[0.73–1.01]), decreased urine albumin-to-creatinine ratio (ACR, coefficient=-0.65, 95 %CI:[-1.22, -0.08]), and increased eGFR (coefficient=1.55, 95 %CI:[0.14, 2.96]). Every 1 % increased CCFD% was significantly associated with increased incidence of CKD (OR=1.72, 95 %CI:[1.14–2.58]) and decrease eGFR (coefficient=-6.47, 95 %CI:[-9.68, -3.26]). Non-linear regression revealed that SVC vessel density was associated with eGFR among patients with advanced retinal microvasculature damage. Conclusions: Retina and choroid blood flow were associated with the onset and severity of CKD. Decreased SVC and decreased CCFD% can be used for non-invasively screening CKD in diabetes patients.